Synthesis of silicone elastomers containing trifluoropropyl groups and their use in dielectric elastomer transducers. Issue 126 (10th December 2015) - Dascalu, Mihaela; Dünki, Simon J.; Quinsaat, Jose-Enrico Q.; Ko, Yee Song; Opris, Dorina M.
Abstract : Polysiloxane elastomers containing varying mo2009l% of trifluoropropyl groups were investigated in dielectric elastomer actuators. Abstract : Vinyl end-functionalized polysiloxanesP x containing varying mol% of trifluoropropyl groups (x) were prepared starting from 1, 3, 5-tris(3, 3, 3-trifluoropropyl)-1, 3, 5-trimethylcyclotrisiloxane (F3 ) and octamethylcyclotetrasiloxane (D4 ) via anionic polymerization in the presence of tetramethylammonium hydroxide (TMAH) and 1, 3-divinyl-1, 1, 3, 3-tetramethyldisiloxane end-capping reagent. Their structures were determined by 1 H NMR spectroscopy and their molecular weights and distributions were measured by GPC. The variousP x were cross-linked in thin films via hydrosilylation of the vinyl groups with tetrakis(dimethylsiloxy)silane cross-linker in the presence of Karstedt catalyst. The mechanical, dielectric and electromechanical properties of the prepared films were investigated. An increase in the permittivity ( ε ′) with increasing content of polar trifluoropropyl groups was observed with a maximum value of ε ′ = 6.4 forP58 (0) . A maximum lateral actuation strain of 5.4% at an electric field as low as 7.8 V μm −1 was measured for a material prepared by cross-linkingP53 .